Outcome of Acute Renal Failure in Neonates and Its Associating Factors - Hamayun Anwar, Momna Heemal, Zarmast Khan, Zafariqbal Bhatti (Pakistan Journal of Medical & Health Sciences, 2022)
Objective:To identify various predisposing causes and immediate consequences in new-borns presenting with acute renal failure. Study design: The study design was case series. Place & duration:In the Pediatric department of Shifa International Hospital, Islamabad for one-year duration from September 2020 to August 2021. Material and Methods:A total of 1300 cases were assessed for acute renal failure (ARF)and 98 established cases of ARF being included in the research. The neonates (0-28 days old) who met the criteria for ARF, i.e., anuria/oliguria plus a serum creatinine level more than 1.5 mg/dl, were included in this research. The patient’s relevant medical history, physical examination, and laboratory tests were recorded on a separate proforma after given informed permission for the procedure. Each patient’s outcome was precisely documented. The statistical software for social sciences was used to examine the data (SPSS20.0). A p-value of less than < 0.05 was considered significant. Results:A total of 98 cases (7.5 percent) were studied, with 68 (69.4 percent) males and 30 (30.6 percent) females. The ratio of males to females was 1.6:1. According to the study results, the mean age was 9.85± 7.20 days and the mean weight was 2.54± 0.65 kg. The majority of the infants were delivered at a hospital (73.5 percent). The most prevalent ARF symptoms in our neonates were birth asphyxia (30.6%), sepsis (24.5%), respiratory distress syndrome (RDS) (11.2%), and dehydration (9.2%), bleeding in (4.1 percent) and meconium aspiration in 3(3.1 percent). CCF and neurogenic bladder were both present in two patients. In 4 individuals, obstructive uropathy was found, including 2 cases of urethral valve (PUV) blockage and 2 cases of pelvic ureteric junction obstruction (PUJO). Neonates with ARF had a 28.5 percent overall death rate (28 cases). Conclusion:When it comes to neonates in critical care, acute renal failure is a frequent concern to observe. More than one predisposing factor for acute renal failure was present in the majority of the patients. Preventing acute renal failure in infants may be accomplished by early identification of risk factors and prompt treatment of underlying diseases.